Determinar la rotación de cultivo para categorizar el valor económico del uso de la tierra en la producción de ciclo corto en la comuna Pechiche de la parroquia Chanduy del cantón Santa Elena - Herrera Sánchez, Lorena Maribell (2013)
Agriculture has been an economical activity of vital importance across the history of humanity, according to FAO 39% of the world’s population consists of agriculture, this has been the prime material of the industrial development of various economies generated, today through agriculture the worlds wishes to eradicate extreme poverty, reduce the number of hungry people in half, all of this has great importance in the agricultural activity which uses various techniques and knowledge to cultivate the soil and get food. Ancestral knowledge, science, and experiments have been conducted to obtain the best results in the productivity of the soil many of them have been proofed efficiently, other have simply exhausted the soil……..